Processing of the English causative-have construction by monolinguals and Brazilian Portuguese-English bilinguals - Clarice Fernandes dos Santos (2019)
This thesis addressed the off-line processing of two causative constructions, one in Portuguese and another in English, by Brazilian Portuguese (BrP) English bilinguals and English monolinguals. Following Construction Grammar theory (GOLDBERG, 1995;2006), the two constructions, which have provision of service as a semantic pole, were analyzed: The Portuguese transitive of subject agent beneficiary (CIRÍACO, 2014a), elaborated by sentences such as Eu cortei o cabelo and the English causative-have, elaboratedby sentences such as I had my hair cut. Vilela (2009) carried off-line experiments using the English construction with monolinguals and bilinguals. She found that bilinguals rejected sentences with a causative sense, meaning that another person performed the action (subject beneficiary), such as I cut my hair (at the salon), more than monolinguals did. This group reported that the SVO use was uncommon, but not impossible in their language. This result is consistent with Goldberg (1995) and inconsistent with the hypothesis that the SVO pattern with a causative meaning is exclusive to Portuguese(CANÇADO, 2010). To contribute to this discussion, the present study aimed at replicating Vilelas findings, through a more refined methodology. English monolinguals and BrP-English bilinguals performed two offline tasks. First, they were asked to read severaltexts of three sentences and answer, on a scale of 1 to 5, how much they agreed with the interpretation in the third sentence, considering the first two. The first sentence was a context (Yesterday, Isabelas car broke down), the second was the target (She fixed the car) and the third was the interpretation to which participants had to respond (Shefixed the car herself). The purpose of this experiment was to verify whether the participants were sensitive to the use of the transitive form (SVO) with a causative meaning, which is common in the bilinguals L1. Besides that, the frequency of the verbs instantiating the construction was controlled: three frequency bands were defined for the verbsused (high, medium and low). In the second task, participants freely completed sentences (cloze task) which elicited the meaning of provision of services, which, in English, is prototypically expressed by the causative-have construction. The use of the transitive formand the choice of the auxiliary verb in causative-have use-cases were also assessed from the second task. Contrary to what was expected from Vilelas study, the first experiment revealed that bilinguals did not express more sensitivity to the use of SVO with causative meaning than monolinguals in any of the frequency bands. The second experiment showed that both bilinguals and monolinguals used transitive sentences when the meaning of provision of services is elicited. As to the use of the prototypical construction of English, the causative-have, while bilinguals tended to prefer have, monolinguals opted for get.